Application of Blockchain Technology at Sekolah Islam Terpadu Al-Madinah - Mohammad Kahfi Abdul Azis; Dewi Wahyuningsih; Patras, Yuyun Elizabeth Patras (LPPM Universitas Terbuka, 2023)
Abstract: The purpose of this study is to discuss Blockchain Technology and the application of Sisko at the Al-Madinah Integrated Islamic School, where the students’ cognitive development varies from 4 years to 17 years old. This article uses the library research method which refers to 19 articles downloaded from Google Scholar and Crossref. Blockchain technology is a system that limits its users according to its boundaries but can still be connected with other users. One of the systems for implementing Blockchain Technology at the Sekolah Islam Terpadu Al-Madinah is Sisko SIT Al-Madinah, which contains a database about education from Kindergarten to High School within the Al-Madinah Integrated Islamic School. The menu in the Sisko system is different for each user, for example students use Sisko for exams and assignments, teachers use Sisko to input grades and savings, principals and vice principals use Sisko to manage curriculum, add and edit student data, map students into classes, and finally the Sisko admin uses it to add and edit report formats, map user accounts and archive school databases. Sisko is highly recommended for schools that want to be more effective and efficient in managing data, finances, learning outcomes and in archiving all of their data because schools must be ready to shift into school digitalization in this era.